Recent Advances in the Multicomponent Synthesis of Heterocycles Using 5-Aminotetrazole - Javahershenas, Ramin; Mei, Haibo; Koley, Manankar; Soloshonok, Vadim A.; Makarem, Ata (Synthesis, 2024)
The unique reactivity and beneficial features of the 5-aminotetrazole synthon (1H-tetrazol-5-amine) have made it a versatile and effective building block in the synthesis of heterocyclic compounds. In addition, several drugs containing this scaffold with a wide array of biological properties have been already introduced. Heterocyclic structures are the backbone of many biologically active and industrially important compounds. 5-Aminotetrazole is one of the favored synthons used in the preparation of heterocycle-bearing compounds, especially in multicomponent synthesis. This review highlights a comprehensive overview of the emerging applications of 5-aminotetrazole as a key component in the synthesis of heterocyclic frameworks through multicomponent reactions, reported between 2017 and July 2023.1 Introduction2 5-Aminotetrazole3 Tetrazolopyrimidine Compounds4 Spiro Compounds5 Miscellaneous6 Conclusion
Keywords: 1H-tetrazol-5-amine; 5-aminotetrazole; heterocycles; multicomponent reactions; synthesis